Reliability and statistics in transportation and communication : selected papers from the 19th International Conference on Reliability and Statistics in Transportation and Communication, RelStat'19, 16-19 October 2019, Riga, Latvia /: selected papers from the 19th International Conference on Reliability and Statistics in Transportation and Communication, RelStat'19, 16-19 October 2019, Riga, Latvia. (©2020) - Unknown
No abstract available